Exploring the potential of Indigenous Australian teaching and learning practices within tertiary coursework to contribute to improved professional practice and social justice - Woods, Glenn (2024)
The purpose of this PhD was to explore what it means when we talk about an Indigenous approach to teaching and learning in practice. This topic is important because the published discussion that currently exists in this space is far from comprehensive, often theoretically considered around pedagogical models but not clear in terms of what it is an Indigenous approach to teaching and learning might include as an experience for learners and teachers. With an increasing recognition of the rights of Indigenous peoples to engage the education space on their own terms, in ways that represent the beliefs, values and aspirations of Indigenous educators, it is important that we have definitions and examples of what an Indigenous education process might look like in contemporary Australian educations contexts, when advocating for and negotiating a place within those spaces. Further to this, it is important to consider how an Indigenous approach to learning and teaching would look like in a specific context, such as a university qualification program, what the potential benefits of this approach are and what the current challenges are in implementing this. The research approach involved engaging twelve culturally diverse First Nations education practitioners, who are committed to the recognition and engagement of Indigenous learning and teaching practices in contemporary education contexts. A yarning research method was utilised to thematically analyse the ways in which these practitioners defined what an Indigenous approach to teaching and learning is in contemporary and contested education spaces. Key findings include a strong consensus amongst culturally diverse First Nations education practitioners around commonly held philosophical beliefs, shared values and shared aspirations regarding how we might define an Indigenous approach to learning and teaching in contemporary practice contexts. The strength of this consensus has led to a suggestion by the researcher that it may be best to define these shared beliefs as an ...